Hermeneutical Reason and Religious Issue: An investigation of Jean Greisch’s Thought - Saleh, Muthana; Al–Haidari, Ehsan (Al-Adab Journal, 2025)
The thesis of hermeneutical reason is of fundamental importance in the overall preoccupations of the French philosopher Jean Greisch, as the various axes of his work on the religious issue are organized according to it in the context of his attempt to establish the field of philosophy of religion in an era of complete nihilism. The truth is that this thesis is the result of the work of a number of philosophers belonging to the hermeneutical phenomenological trend in the contemporary era, and whose works are necessary stepping stones towards enabling the systematic establishment of the hermeneutical mind. From this perspective, Greisch is credited with his explicit formulation of the term (the era of hermeneutical reason), and his tireless work to integrate these various works into the context of an innovative vision that suits the requirements of philosophy in its current era.     This research aims to present a philosophical approach to the hermeneutic mind thesis proposed by Greisch, in terms of describing its historical conditions: that is, Its relationship to the phenomenon of secularization and the processes of dismantling the mythical vision in the human sciences, and its direct connection to suspicious tendencies in the philosophical field. In addition to that, an analysis of its basic foundations and theoretical scheme, which the philosopher worked hard to establish in a number of his late works. This entails following the historical transformations and decisive turning points that phenomenology, hermeneutics, and philosophical anthropology alike went through, up to the moment when it was possible to cultivate the interpretive act within phenomenological intuition.